Three-Dimensional Poly-(ε-Caprolactone) Nanofibrous Scaffolds Promote the Maturation of Human Pluripotent Stem Cells-Induced Cardiomyocytes - Zhang, Mingming; Xu, Yuerong; Chen, Yan; Yan, Qinru; Li, Xiaoli; Ding, Lu; Wei, Ting; Zeng, Di (Frontiers in Cell and Developmental Biology, 2022)
Although pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) have been proved to be a new platform for heart regeneration, the lack of maturity significantly hinders the clinic application. Recent researches indicate that the function of stem cell is associated with the nanoscale geometry/topography of the extracellular matrix (ECM). However, the effects of 3D nanofibrous scaffolds in maturation of iPSC-CMs still remain unclear. Thus, we explored the effects of restructuring iPSC-CMs in 3D nano-scaffolds on cell morphology, cardiac-specific structural protein, gap junction and calcium transient kinetics. Using the electrospinning technology, poly-(ε-caprolactone) (PCL) nanofibrous scaffold were constructed and iPSC-CMs were seeded into these forms. As expected, strong sarcolemmal remodeling processes and myofilament reorientation were observed in 3D nano-scaffolds culture, as well as more expression of cardiac mature proteins, such as β-MHC and MLC2v. The mature morphology of 3D-shaped iPSC-CMs leaded to enhanced calcium transient kinetics, with increased calcium peak transient amplitude and the maximum upstroke velocity (Vmax) . These results proved that the maturation of iPSC-CMs was enhanced by the electrospun 3D PCL nanofibrous scaffolds treatment, proved by the structural and functional changes. These findings not only highlight the biophysical role of 3D nanofibrous scaffolds in the maturation of iPSC-CMs, but also enable us to design a feasible strategy to improve the myocardium bioengineering by combining stem cell with scaffold.